In vivo muscle mechanics during human locomotion - Ishikawa, M. (Studies in Sport, Physical Education and Health, 2005)
The present series of studies were designed to examine how the interaction between muscle fibers and tendinous tissues (TT) were modulated for effective utilization of elastic energy during stretch-shortening cycle (SSC) exercises. By combining the in vivo direct recordings of tendon force with fascicle length changes by the ultrasonic techniques, the in vivo behavior of the vastus lateralis and triceps surae muscle groups was examined in several different intensity drop jumps äs well äs in walking and jogging. In addition, the in vivo architectural changes of fascicle-TT due to the exhausting SSC-induced fatigue were studied. The results suggest that there is intensity specific fascicle-TT interaction in the process of elastic energy utilization during SSC exercises. This intensity specificity is related to the fascicle stiffness operating to influence the power enhancement during the push-off phase of the SSC exercises. However, the efficacy of elastic recoil of TT can be limited by the drop intensity and /or contact time. In addition, the fascicles in the bi-articular (medial gastrocnemius; MG) muscle cannot necessarily show the SSC behavior in the same way as in the mono-articular muscles (VL). In comparison of the fascicle-tendon interaction between walking and jogging, the spring-like bouncing äs in jogging and the catapult action as in walking were observed in the TT behavior. The process of the TT stretch-recoil can thus be different between these activities. This fascicle behavior can consequently be modified depending on the movement pattern to utilize the elasticity of TT effectively.